Effect Of Cutting Parameters On Tool LifeTin CoatedCarbide In Turning Dry Machining Of TEW 6582 Steel By Aplication Metode Taguchi - SuhardiNapid; Ahmad Bakhori; Abdul Haris Nasution; Mhd.Rafiq Yanha; Khairul Suhada; M.Fahreza; M.Zein Pane (International Journal of Health Engineering and Technology, 2026)
The tool life limit is determined by the tool wear dimension. The tool life will increase as the tool wear increases. Turning experiments were carried out by varying the cutting speed, cutting depth, feed and cutting angle of the tool, while the tool life was evaluated based on the tool flank wear criteria. The purpose of the study was to determine the magnitude of the tool life in dry machining of TEW 6582 steel with various cutting conditions. To study the tool life, 9 cutting conditions were first determined, namely cutting speed 200 m/min, 250 m/min, 300 m/min; feed 0.15 mm/r, 0.2 mm/r, 0.25 mm/r and cutting depth 1 mm, 1.5 mm, 2 mm. Edge wear (VB) 0.1 mm, 0.3 mm and 0.5 mm and measured using an optical microscope. Experimental data were processed and analyzed using the Taguchi L9 method (34). Cutting speed has a significant effect on tool life, where increasing cutting speed substantially reduces tool life. Depth of cut and feed rate also contribute to tool wear, although to a lesser extent than cutting speed. The results show that the optimum cutting conditions are obtained by dry machining at a cutting speed of 200 m/min, a depth of cut of 1.0 mm, a feed of 0.15 mm/r and a tool geometry of 6o. This cutting condition gives a tool life of 2.456 second (40.9 minutes). When this cutting condition is carried out with wet machining, it is found that the tool life is 2.591 second (43.1 minutes). So the difference in tool life between dry and wet machining is not significant so that dry machining is feasible for the manufacturing industry.